Reasoning The Character of Hayy Ibn Yaqdzan: a Human Raised by a Deer in The Study of Philosophical Literature - Ramdon Dasuki, Mohamad; Hakim, Lukmanul (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2025)
This article aims to explore and analyze the philosophical dimensions within the classical novel Hayy ibn Yaqzan by Ibn Tufail through the lens of literary philosophy. The objective is to analyze how philosophical themes such as the nature of life, self-awareness, human uniqueness, and the search for truth are embedded within a literary narrative. Using a philosophical-literary method, this research interprets the symbolic and imaginative elements in the novel by applying both philosophical inquiry and literary analysis. The method involves examining the character development, internal conflicts, and narrative structure of the protagonist, Hayy, in relation to broader philosophical questions. The results reveal that Hayy ibn Yaqzan is not merely a work of fiction but a narrative deeply infused with philosophical reflection. The novel presents a rich exploration of human consciousness, ethical reasoning, and metaphysical inquiry through allegorical storytelling. Furthermore, the analysis indicates that philosophical literature can serve as a powerful tool to bridge imaginative fiction with rational thought, demonstrating that literary works can embody both artistic expression and intellectual depth